Exploring Student Learning Behavior to Increase Digital Language Learning Apps Usability: A Case Study - Putri, Marisca Revani; Wiharja, Chandra Kurniawan; Luke, Joice Yulinda; Wishnoebroto, Wishnoebroto (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
The advancement of technology and the impact of Covid 19 had led to student’s learning behavior shift from conventional to digital learning approaches. The utilization of technology in English language teaching played important roles in facilitating learning to suit the current student’s learning behavior. The study aimed to find out the features in language learning apps that might be suitable with the student’s learning behavior. A case study approach was employed to collect the data and reach the conclusion. Data was collected through e-surveys to 75 university students who experienced in using language learning apps to find out their learning behavior after pandemic and to investigate the features that should be developed to facilitate student’s learning. Result found eleven (11) expected features that should be available on English language learning apps. Yet, the result also revealed that the students still need the teachers and interaction to facilitate their learning activities.